Understanding the financial burden of incomplete abortion: An analysis of the out-of-pocket expenditure on postabortion care in eight public-sector health care facilities in Dakar, Senegal. Issue 9 (2nd September 2022) - Baynes, Colin; Diadhiou, Mohamed; Lusiola, Grace; O'Connell, Kate; Dieng, Thierno
ABSTRACT: Timely access to treatment is essential for women when they experience abortion complications. Out-of-pocket (OOP) expenditure is a known barrier to health care access. In 2018, we assessed the financial burden of accessing postabortion care (PAC) borne by women in Dakar, Senegal, where studies estimate that half of poor women with complications obtain PAC. We interviewed 729 women following discharge from PAC. Women reported expenditures on transportation, admission, treatment, family planning, hospitalisation, complementary tests, prescriptions, other medicines and materials. We compare women's OOP on PAC by expenditure category, type of treatment and facility type, and use multiple generalised linear regression analysis to explain variation in overall OOP and forecast it under alternate scenarios. The average OOP was USD $93.84. At health centres it was $65.47 and at hospitals it was $120.47. The average cost of PAC using dilation and curettage was $112.37, manual vacuum aspiration was $99.84, and misoprostol $61.80. Overall OOP on PAC amounts, on average, to 15% of the average monthly salary for women living in Dakar. Strategies that emphasise timely access to misoprostol for treating complications in primary care settings will address the contribution of OOP costs to Senegal's appreciable unmet need for PAC among the poor.